Ambient condition-processing strategy for improved air-stability and efficiency in mixed-cation perovskite solar cells. Issue 6 (14th August 2020) - Asuo, Ivy M.; Gedamu, Dawit; Doumon, Nutifafa Y.; Ka, Ibrahima; Pignolet, Alain; Cloutier, Sylvain G.; Nechache, Riad
Abstract : Fabrication of efficient halide perovskite solar cells under ambient conditions and their stability remain a challenge due to the sensitivity of halide perovskites to moisture, oxygen, light, and temperature. Abstract : Fabrication of efficient halide perovskite solar cells under ambient conditions and their stability remain a challenge due to the sensitivity of halide perovskites to moisture, oxygen, light, and temperature. Thus, there is a strong demand and interest to develop a method for fabricating perovskite solar cells with long-term stability and even better, such a fabrication method under ambient conditions. To this end, we use a chemical synthesis method and a solvent engineering technique to optimize halide perovskite thin film deposition in an ambient environment. We obtained pinhole-free films composed of large crystal grains and high crystal quality that result in excellent optoelectronic properties of the halide perovskite. We also report a low trap-density in the order of 10 15 cm −3 for the polycrystalline perovskite thin film. Moreover, with an n–i–p solar cell structure, a maximum power conversion efficiency of ∼20.3% with excellent stability in ambient air (25–55%RH) for more than ten months of storage (>7000 hours) is achieved. The optimized solar cell without encapsulation retained ∼80% of its initial performance after ten months of storage with a T 80 of ∼5035 hours. Our findings suggest that the performance and stability of the perovskite solar cells are highly dependent on the device architecture, grain morphology, trap density, and carrier mobility in the device before and after storage.